2021
DOI: 10.4069/kjwhn.2021.06.20
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a couple-centered antenatal education program in Korea

Abstract: This study was conducted to develop a couple-centered antenatal education program and to test the program's feasibility. Methods: With a preliminary-experimental study design, 33 pregnant couples who were expecting their first child participated in this study. The program consisted of four sessions (1 hour/session/ week) of education and counseling. Data were collected before and after the intervention from September 2018 to April 2019 at a women's hospital in Daejeon, Korea, with demographic data forms,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The reasons for excluding seven studies from the review were as follows: three studies had provided the same prenatal education to the intervention and the control groups [ 51 , 52 , 58 ], one study was designed as a single-group study before and after the intervention [ 54 ], one paper’s full text was out of our reach [ 53 ], two paper had used interventions different from those intended in the present study [ 55 , 56 ], and one paper was in the Indonesian language [ 57 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for excluding seven studies from the review were as follows: three studies had provided the same prenatal education to the intervention and the control groups [ 51 , 52 , 58 ], one study was designed as a single-group study before and after the intervention [ 54 ], one paper’s full text was out of our reach [ 53 ], two paper had used interventions different from those intended in the present study [ 55 , 56 ], and one paper was in the Indonesian language [ 57 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to inform women about effective coping strategies for stress during pregnancy. A previous study reported that depression was decreased among pregnant women by providing prenatal education intervention about physical and psychological adaptation, delivery preparation, infant care, and spousal relationships [31], which suggests directions for interventions for perinatal women and their families. Nurses can evaluate the factors associated with prenatal depression before and after pregnant women's prenatal health checks and satisfy women's and family members' psychosocial needs through education and counseling.…”
Section: Discussionmentioning
confidence: 97%
“…The content on couple-relationship adaptation included emotional intimacy, support, respect, empathy, gratitude, and emotional exchange between couples from pregnancy to the postpartum period. [ 24 ] Common aspects of training in their study and ours were performing attachment behaviors as well as support and empathy during pregnancy.…”
Section: Discussionmentioning
confidence: 98%